A geografia dos Arranjos Produtivos Locais (APLs) em Alagoas: os APLs do setor industrial – 2004/2015 - Santos , Ezequias Francisco dos (2016)
This studyhas aims to analyze the geography of Arrangements ProductivesPlaces (APPs), even as the actions Mobilization Program for the growth of Arrangements Productives Places from Alagoas (APPA),highlighting the arrangements of industrial sector in period at 2004 until 2015.The research is based in the theoretical and methodological suggestion developed by Santos (2008a; 2008b), to analyze the formation socio-spatial from Alagoas; and Cholley (1964a; 1964b), to examine the spatial of arrangements inAlagoas region. beyond thatto argue the influence of regional development theories on formulationof the concept and typologyof APLs. Ultimately, highlightingthat this type politics has a significant stake in volume composition of jobs and MPEs in the industrial sector, this contributing to the local development of municipalities Alagoas.